Construção e caracterização de um minibiossensor potenciométrico para determinação de adrenalina em amostras de interesse farmacêutico - Mataveli, Lidiane Raquel Verola (2007)
Polyphenoloxidase (PPO) is a cupric enzyme that catalyzes the oxidation of diphenols in quinones and is widely distributed among the vegetables. The activity of this enzyme was measured for a biosensor construction for adrenaline determination, and the banana (Musa sp.) extract presented better results. The calculation of the enzymatic activity provided a value of 974 UA (Units of Activity). It was constructed biossensor with: carbon paste containing 50 UA in phosphate buffer (pH=7,00), into stainless steel needles or polyethylene tube. Slow reestablishment of the baseline was evidenced and it was corrected with the addition of H2O2 to the solution, decreasing the return time to 10 minutes. The biosensor (with polyethylene) provides a linear range from 8,00x10-9 to 8,00x10-4 mol L-1 (LOD = 8,00x10-9 mol L-1) in buffer solution for adrenalin. The results obtained with the proposed method and the Farmacopéia Brasileira (1977) was in agreement. For blood samples, using matrix matching calibration, the linear range was from 8,00x10-7 to 8,00x10-3 mol L-1 (LOD = 8,00x10-7). In the recovery tests, 89,4% of the added value was obtained. In vivo studies, electrodes were inserted in the jugular vein of the Wistar rat and showed promising results.